A Biomimetic Nonantibiotic Nanoplatform for Low‐Temperature Photothermal Treatment of Urinary Tract Infections Caused by Uropathogenic Escherichia coli. Issue 3 (7th January 2022) - Wenjie, Shi; Jinxia, An; He, Tan; Mengran, Jia; Hui, Gao
Abstract: Urinary tract infections (UTIs) caused by uropathogenic Escherichia coli (UPEC) remain a matter of concern, as the clinical use of multiple antibiotics induces antibiotic resistance in bacteria, resulting in the failure of treatments. Despite the emergence of anti‐adhesion strategies that can prevent the development of bacterial drug resistance, these strategies are mainly used for disease prevention rather than effective treatment. Photothermal therapy (PTT) has emerged as an efficient alternative for the elimination of bacteria. Nevertheless, high local temperatures related to PTT probably cause damage to surrounding healthy tissue. Herein, a biomimetic nonantibiotic nanoplatform for low‐temperature photothermal treatment of UTIs is developed. The nanoplatform comprises polydopamine (PDA) photothermal core and biphenyl mannoside (Man) shell with multivalent high‐affinity to UPEC. Scanning electron microscope (SEM) shows PDA‐Man possessed ultra‐strong targeting binding ability toward UPEC. It is the fact that this impulse UPEC to form a large bacterial cluster. Consequently, the high photothermal energy of the PDA‐Man appears predominantly in the affected bacterial area, while the overall environment remains at a low temperature. The fabricated nanoplatform shows excellent photothermal bactericidal effects, approximately 100% in a UTI model. Overall, this low‐temperature photothermal nanoplatform provides an appropriate strategy for the elimination of bacteria in clinical applications. Abstract : A simple and facile antibacterial nanoplatform is developed by conjugating mannoside (Man) ligand on polydopamine (PDA). The designed PDA‐Man presents a low‐temperature photothermal bactericidal effect. The low‐temperature photothermal bactericidal performance results from multivalent Man bind toward uropathogenic Escherichia coli (UPEC) and the photothermal effect of PDA, which greatly avoid the damage of the surrounding normal tissue.